Respuesta :
- First term =9-3=6
- Second term=9
- Common difference=3
So
- a=6
- d=3
Explicit formula
[tex]\\ \rm\Rrightarrow a_n=a+(n-1)d[/tex]
[tex]\\ \rm\Rrightarrow a_n=6+3(n-1)[/tex]
Answer:
[tex]\sf a_n=3n+3[/tex]
Step-by-step explanation:
An explicit formula for an arithmetic sequence allows you to find the nth term of the sequence.
A recursive formula for an arithmetic sequence allows you to find the nth term of the sequence provided you know the value of the previous term in the sequence.
Explicit formula
[tex]\sf a_n=a+(n-1)d[/tex]
where:
- [tex]\sf a_n[/tex] is the nth term
- a is the first term
- n is the number of the term
- d is the common difference
Given:
- [tex]\sf a_2=9[/tex]
- d = 3
- n = 2
Substituting these values into the formula to find a:
[tex]\implies \sf 9=a+(2-1)3[/tex]
[tex]\implies \sf 9=a+3[/tex]
[tex]\implies \sf a=6[/tex]
Therefore the formula is:
[tex]\implies \sf a_n=6+(n-1)3[/tex]
[tex]\implies \sf a_n=6+3n-3[/tex]
[tex]\implies \sf a_n=3n+3[/tex]